Comparison of knowledge non-medical and medical students about the sport of people with disabilities - Agnieszka Jacykowska; Magdalena Gębska (Kazimierz Wielki University, 2018)
Introduction and aim: Physical activity is a very important part of everyone's life. It has positive effect on the functioning of the body of both healthy people and people with disabilities. Many disabled people take competitive sports with very good results. These individuals can find support in a number of organizations cooperating with disabled athletes. The main aim of this article is to compare the knowledge of students of medical and non-medical universities about sport of disabled people. Material and methods: Research was carried out among students of medical and non-medical universities. Tested 152 people - 93  women and 59 men. Diagnostic survey questionnaire method was used during the test. The questionnaire consisted of 17 questions and specifications relating to sport for the disabled. Results: The definition of a disabled person were able to identify by 70% of the surveyed students. 42% of respondents could not indicate the names of the disabled athlete. The majority of respondents (medical and non-medical professions) have seen competition of disabled people on television or the Internet. Rehabilitation and improvement of mental health, were indicated by respondents as the most important benefits of doing sport for disabled. Conclusions: The level of knowledge of students about sport for the disabled can be considered as satisfying.